THE ENERGY EQUIVALENCE PRINCIPLE FOR CALCULATION OF WATER SUPPLY NETWORKS WITH MANY AREAS - V I Shcherbakov; H C Nguyen (RUDN Journal of Engineering Research, 2016)
Existing methods of hydraulic calculation of water supply looped networks is considered mainly transmission and distribution lines, without considering dead-and areas. In the design of water supply systems must take into account the area and configuration of the area, population density, height of buildings, standards of water consumption and other parameters that influence the hydraulic calculation of water supply networks. The principle of energy equivalenting allows to unite a plurality of dead-and areas, designating them as a fictitious line subsystem, which greatly simplifies the calculation of the whole scheme of the full length of the hydraulic system.